Vliv kyslíku na produkci endotoxinu u bakterií ze skupiny Bacteroides fragilis group izolovaných od pacientů s kolorektálním karcinomem - Chmelař, D; Hájek, M; Janečková, J; Vobejdová, J; Martineková, P; Kašíková, A (Epidemiologie, mikrobiologie, imunologie, 2016)
OBJECTIVE: The aim of the study was to draw attention to the risk posed by anaerobic bacteria of the Bacteroides fragilis (BAFR) group, isolated particularly from abdominal lesions, and to assess the possible role of these species in colorectal cancer. A correlation has previously been suggested between the detection of the bacteria of the genus Bacteroides in patients on a meat-based diet and intestinal and, in particular, colorectal cancer. Given that the species of the BAFR group are major producers of endotoxins, measurements and statistical analysis of endotoxin production were used to compare the Bacteroides strains isolated from clinical specimens of patients with colon cancer, rectal cancer, and other abdominal lesions. MATERIALS AND METHODS: Endotoxin production was detected in bacterial strains of the BAFR group (B. fragilis, B. thetaiotaomicron, B. distasonis, and B. vulgatus) isolated from clinical specimens of patients with rectal cancer, colon cancer, and intestinal cancer and was compared with that in strains from samples of patients with inflammatory conditions (anal abscess, appendicitis, skin abscess, etc.) under anaerobic and microaerophilic (with 5% of oxygen) culture conditions. The production of endotoxins was detected quantitatively using the Pyrosate LAL assay kit (Limulus Amoebocyte Lysate Test, BIOGENIX, CR) in four species of the BAFR group after anaerobic and microaerophilic culture. Five strains of each isolated Bacteroides species from each type of specimens were tested (in total 140 BAFR strains). The amount of endotoxin was given in endotoxin units per ml (EU/ml). RESULTS: Endotoxin production by bacteria under microaerophilic culture conditions was several times higher in comparison with strictly anaerobic culture.The difference was statistically significant (F1.269 = 160, p <0.0001). As regards the effect of oxygen on endotoxin production, the amount of endotoxins produced under microaerophilic culture conditions (average 889.1 EU/ml) was 2.5 times as high as that observed under anaerobic culture conditions (358.2 EU/ml), regardless of the bacteroides species and diagnosis. These results suggest that the amount of free oxygen in the environment affects the amount of endotoxin generated by the Bacteroides strains. CONCLUSION: The results show that endotoxin production by the Bacteroides strains under microaerophilic culture conditions is several times as high as that under strictly anaerobic culture conditions.
Keywords: Endotoxins; Bacteroides fragilis; Oxygen; Bacteroides fragilis group - endotoxins - colorectal carcinoma.; kyslík; Humans; kolorektální nádory; lidé; Diet; dieta; Colorectal Neoplasms; endotoxiny